2019
DOI: 10.12659/msm.913634
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of G Protein-Coupled Estrogen Receptor (GPER) is Associated with Reduced Prognosis in Patients with Gastric Cancer

Abstract: Background This study is aimed to investigate the prognostic significance of the expression of G protein-coupled estrogen receptor (GPER) in gastric cancer tissue using bioinformatics data and immunohistochemistry. Material/Methods Expression of GPER mRNA in gastric cancer tissues and normal adjacent tissues was investigated using data from The Cancer Genome Atlas (TCGA), the Gene Expression Omnibus (GEO), and Oncomine database. Kaplan-Meier Plotter identified the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Among the six energy metabolism-related genes, DYNC1I1, GPER1, MFAP2, C3, and GLI1 were risk factors while ARRB1 was a protective factor for clinical outcomes in GC. The prognostic value of the ve risk genes have been sporadically reported in previous studies, while the protective value of ARRB1 in GC was rarely identi ed [44][45][46][47][48][49]. Functional enrichment analysis revealed that this metabolism-related signature was signi cantly involved in some classical cancerrelated pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Among the six energy metabolism-related genes, DYNC1I1, GPER1, MFAP2, C3, and GLI1 were risk factors while ARRB1 was a protective factor for clinical outcomes in GC. The prognostic value of the ve risk genes have been sporadically reported in previous studies, while the protective value of ARRB1 in GC was rarely identi ed [44][45][46][47][48][49]. Functional enrichment analysis revealed that this metabolism-related signature was signi cantly involved in some classical cancerrelated pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Among them, 33 articles were subsequently removed either because the data cannot be extracted, or the studies did not provide immunohistochemistry results. Finally, 20 articles were included in this meta-analysis [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The characteristics of the included studies are shown in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, bioinformatics data showed that GPER DNA promoter methylation may be involved in the reduced expression of GPER in GC and that GPER may act as a tumor suppressor through the regulation of the epithelial–mesenchymal transition (EMT) pathway. 76 Another study similarly indicated that GPER mRNA levels were significantly lower in GC tissues than in normal tissues, and a stage-dependent decrease was found in the GPER expression of GC on the basis of GPER fluorescence intensity in cancer stages I and II (45% and 30%) versus stages III and IV (25% and 20%, respectively). 77 The induction of pERK-dependent endoplasmic reticulum stress via GPER signaling may increase G1’s chemotherapeutic effect in the GC cells.…”
Section: Gper In Gastric Cancer (Gc)mentioning
confidence: 93%
“…Tian et al 76 demonstrated that GPER mRNA and protein levels were downregulated in GC tissues and cells, and the decreased expression of GPER protein was an independent risk factor for poor prognosis in patients with GC. Furthermore, bioinformatics data showed that GPER DNA promoter methylation may be involved in the reduced expression of GPER in GC and that GPER may act as a tumor suppressor through the regulation of the epithelial–mesenchymal transition (EMT) pathway.…”
Section: Gper In Gastric Cancer (Gc)mentioning
confidence: 99%